Wpływ zmian w systemie emerytalnym w Polsce w latach 2011–2013 na efektywność inwestycji otwartych funduszy emerytalnych - Buchowiec, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The purpose of the article is to present and discuss the most important changes in the Polish pension system implemented in 2011–2013 — in particular regarding its capital part. The first part of the article describes the main legal changes introduced in the analysed period, and the second part focuses on their impact on the effectiveness of investments made by open pension funds. The analysis shows that analyzed legal changes can negatively influence not only the sector of open pension funds itself and their investments, but also the long-term financial stability of the Polish pension system.
Keywords: polski system emerytalny; otwarte fundusze emerytalne (OFE); efektywność inwestycji